Road Pricing Effect on the Emission of Traffic Pollutants, a Case Study in Tehran - Hadji Hosseinlou, Mansour; Zolfaghari, Abbas; Yazdanpanah, Mahdi (Salehan Institute of Higher Education, 2016)
Road pricing is one of the main purposes of traffic management policies in order to reduce personal car use. Understanding the behaviour of drivers under the impact of the road pricing policy, can assist transportation planners in making better and more efficient decisions. This research aims at investigating the reactions of private car users to road pricing using stated preference (SP) method on the one hand, and on the other hand, studies the road pricing effect on traffic flow and pollutants. To this aim, the acceptance rate of pricing, which is obtained from modeling of survey data, as well as real traffic flow data in Shahid Hemmat Highway in Tehran, Iran, are applied as the simulation software input. Based on the results of this research, at the lowest price (TN11000), the contribution of toll acceptance is equal to 64/91 percent. The fuel consumption rate at this price decreases to 49/91% and the emission rate of CO2, NOx, particle material (PM) and volatile organic compounds (VOCs) pollutants decrease to 56.82%, 49.46%, 36.8% and 63.17%, respectively. At the highest price (TN10000), toll acceptability, fuel consumption, CO2, NOx, PM and VOC emission rates decrease to 5.47%, 3.57%, 3.98%, 2.85%, 1.22% and 4.86%, respectively.